A comparative study on roles of natural killer T cells in two diet-induced non-alcoholic steatohepatitis-related fibrosis in mice. (31st December 2022) - Zheng, Shumei; Yang, Wenzhuo; Yao, Dongmei; Tang, Shanhong; Hou, Juanni; Chang, Xing
Abstract: Background: Immune responses are important in the progression of non-alcoholic fatty liver disease (NAFLD). Natural killer T (NKT) cells are main components of the innate immune system that modulate immunity. However, the role of NKT cells in NAFLD remains controversial. Objective: We aimed to investigate the role of NKT cells in non-alcoholic steatohepatitis (NASH)-related fibrosis in fast food diet (FFD)- and methionine choline-deficient (MCD) diet-induced mouse models. Methods: Hepatic NKT cells were analysed in wild-type (WT) and CD1d-/- mice fed FFD or MCD diets. Hepatic pathology, cytokine profiles and liver fibrosis were evaluated. Furthermore, the effect of chronic administration of α-galactosylceramide (α-GalCer) on liver fibrosis was investigated in both FFD- and MCD-treated mice. Results: FFD induced a significant depletion of hepatic NKT cells, thus leading to mild to moderate NASH and early-stage fibrosis, while mice fed MCD diets developed severe liver inflammation and progressive fibrosis without a significant change in hepatic NKT cell abundance. FFD induced a similar liver fibrogenic response in CD1d-/- and WT mice, while MCD induced a higher hepatic mRNA expression of Col1α1 and TIMP1 as well as relative fibrosis density in CD1d-/- mice than WT mice (31.8 vs . 16.3, p = .039; 40.0 vs . 22.6, p = .019; 2.24 vs . 1.59, p = .036). Chronic administration of α-GalCer induced a higher hepatic mRNA expression of TIMP1 in MCD-treated mice than controls (36.7 vs. 14.9, p = .005). Conclusion: NKT cells have protective roles in NAFLD as the disease progresses. During diet-induced steatosis, mild to moderate NASH and the early stage of fibrosis, hepatic NKT cells are relatively depleted, leading to a proinflammatory status. In severe NASH and the advanced stage of liver fibrosis, NKT cells play a role in inhibiting the NASH-related fibrogenic response. Chronic administration of α-GalCer induces NKT cell anergy and tolerance, which may play a role in promoting the liver fibrogenic response.